PERSEPSI DAN TANTANGAN PENGEMBANGAN KINERJA PRAMUWISATA LOKAL MELALUI PELATIHAN : STUDI KASUS DESA ENDE - Moh Azhar Amin; Isdar Wahim; Jumraidin, Jumraidin (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to explore the perceptions and challenges in the development of local tour guide performance through training in Ende Tourism Village, Central Lombok. This case study provides an overview of the success of West Nusa Tenggara Province in managing tourism as a cultural heritage beneficial to the community. Ende Village, with its cultural richness and natural beauty, holds significant tourism potential. However, local tour guides in Ende still face complex challenges, particularly in enhancing foreign language skills after initial training. Despite this, significant opportunities arise with the frequency of visits by foreign tourists, yet the threat of increasing competition underscores the need for innovative and proactive marketing strategies. Therefore, this study proposes to delve into the perceptions of local tour guides regarding the training they receive and identify key obstacles to be addressed, focusing on SWOT analysis to understand strengths, weaknesses, opportunities, and threats in the development of local tourism in Ende Village